PENINGKATAN KUALITAS PEMBELAJARAN IPS DENGAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK TWO STAY-TWO STRAY PADA SISWA KELAS IV SD TAMBAKAJI 05 KECAMATAN NGALIYAN KOTA SEMARANG - Indriyani, Cici (KREATIF, 2011)
Based on preliminary observations in elementary Tambakaji Ngaliyan Semarang District 05 found problems in learning social studies teacher in fourth grade that is less varied in using learning methods. Teachers not only explain the material and use of learning media. Many things are abstract in the IPS so that learning is not suitable if the material presented in the conventional course. Learning is too monotonous and less involved students, so students are passive, impact students interest in learning social studies is lacking. This led to student learning outcomes are still low. Formulation of the problem in this study were: (1) Does the model of cooperative learning techniques two stay-two stray elementary school teachers can improve their skills in teaching Tambakaji 05? (2) Does using the model of cooperative learning techniques two stay-two stray fourth grade student activity Tambakaji 05 can be increased? (3) Does using the model of cooperative learning techniques two stay-two stray students fourth grade Tambakaji 05 will increase?. Classroom Action Research objectives are: (1) To improve teachers skills in teaching social studies with a model of cooperative learning techniques two stay-two stray in District 05 Elementary Tambakaji Ngaliyan Semarang City. (2) To enhance the learning activities of students in the IPS model of cooperative learning techniques with two stay-two stray on the SD 05 District Tambakaji Ngaliyan Semarang City (3) To improve learning outcomes in students social studies fourth grade Tambakaji District 05 Ngaliyan Semarang City. The research was conducted in the second study cycle, each cycle consists of planning, implementation of action, observation, and reflection. Research subjects is the Teacher and Students fourth grade Tambakaji 05, amounting to 29 students consisting of 15 male students and 14 female students. The variables of this study is teacher skills, student activities, and student learning outcomes. Tool used is the test data, observations, field notes, and documentation. Analysis of the data in this classroom action research using quantitative and qualitative analysis. The results of this study showed an average score of skills of teachers in the cycle I 2.8 with an average percentage of 70% with good category and the average score of 3.3 second cycle teachers skills with the percentage of 83% in the category very well. average score of student activity in the cycle I 2.85 with the percentage of 71% in the category of good and cycle II 3.22 with the percentage of 80.5% in the category very well. Exhaustiveness learning outcomes of the cycle I and cycle II increased. Exhaustiveness classical learning of students in the initial conditions before the action has only 51%. Having done the action research cycles I exhaustiveness classical to 69%. After a second cycle of exhaustiveness classical action showed 83%, or as many as 23 students who have thoroughly studied. Based on the results of these studies can be concluded that the model of cooperative learning techniques with two stay-two stray can improve the quality of teaching social studies in fourth grade students Tambakaji 05 Ngaliyan District of Semarang. From the research it is advisable for teachers to use cooperative learning techniques model a two stay-two stray in teaching social studies as well as trying on other subjects. Keywords: Quality of teaching Social Studies, Engineering Cooperative Two stay-Two Stray